2019
DOI: 10.1101/2019.12.20.882423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bovine breed-specific augmented reference graphs facilitate accurate sequence read mapping and unbiased variant discovery

Abstract: BackgroundThe current bovine genomic reference sequence was assembled from the DNA of a Hereford cow.The resulting linear assembly lacks diversity because it does not contain allelic variation. Lack of diversity is a drawback of linear references that causes reference allele bias. High nucleotide diversity and the separation of individuals by hundreds of breeds make cattle ideally suited to investigate the optimal composition of variation-aware references. ResultsWe augment the bovine linear reference sequence… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 85 publications
(127 reference statements)
2
7
0
Order By: Relevance
“…PacBio HiFi reads for a Nelore x Brown Swiss bull are available at study accession PRJEB42335 under sample accession SAMEA7765441. Data supporting this study, including the multi-assembly graph, non-reference sequences, putatively novel genes, transcript abundances and sequence variants detected from non-reference sequences are available via Zenodo (https://doi.org/10.5281/zenodo.4385983) 68 .…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…PacBio HiFi reads for a Nelore x Brown Swiss bull are available at study accession PRJEB42335 under sample accession SAMEA7765441. Data supporting this study, including the multi-assembly graph, non-reference sequences, putatively novel genes, transcript abundances and sequence variants detected from non-reference sequences are available via Zenodo (https://doi.org/10.5281/zenodo.4385983) 68 .…”
Section: Data Availabilitymentioning
confidence: 99%
“…Efforts to mitigate reference allele bias and increase the genetic diversity of reference genomes have led to graph-based references 14,15 . We have previously shown that a bovine genome graph, which integrates linear reference coordinates and pre-selected variants, improves the mapping of reads and enables unbiased variant genotyping 16,17 . However, previous attempts focused on augmenting the bovine reference genome with small variations (<50bp), not the larger class of structural variations.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, errors and gaps in the functional annotations of bovine reference-quality assemblies other than ARS-UCD1.2 are a major obstacle to switch references. TThe application of an augmented reference genome that contains ARS-UCD1.2 and its functional annotations as backbone as well as variants detected in other assemblies might solve such problems [12,45].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, read alignments may be erroneous particularly at genomic regions that differ substantially between the sequenced individual and the reference genome [10]. The use of consensus reference genomes or variation-aware reference graphs may mitigate this type of bias [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation